INSTRUMEN BERBASIS HOTS UNTUK MENGIDENTIFIKASI KEMAMPUAN PEMAHAMAN SOAL MATEMATIKA MATERI PECAHAN - Aurelia, Davina (FIBONACCI: Jurnal Pendidikan Matematika dan Matematika, 2024)
Problem-solving skills are one of the 21st-century skills that involve higher-level cognitive abilities, commonly referred to as HOTS (Higher Order Thinking Skills). This research aims to develop HOTS-based instruments on fraction material for elementary school students. This development research was conducted using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The data collection methods used are interviews, questionnaires, and documentation. The data obtained from the expert material validation and teacher validation were analyzed descriptively and quantitatively by calculating the inter-rater reliability. Based on the analysis results, the HOTS question instrument received a very good qualification in terms of validity, reliability, and alignment with the aspects of content, construct, and language. Based on this analysis, the HOTS question instrument on fractions is suitable for use in learning evaluation.